2014
DOI: 10.1080/09593330.2014.894581
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of gas-phase organic contaminants via nitrogen-embedded one-dimensional rod-shaped titania in a plug-flow reactor

Abstract: In this study, one-dimensional rod-shaped titania (RST) and nitrogen-doped RST (N-RST) with different ratios of N to Ti were prepared using a hydrothermal method and their applications for purification of indoor toxic organic contaminants in a plug-flow reactor were examined under visible or ultraviolet (UV) irradiation. The surface characteristics of as-prepared photocatalysts were investigated by transmission electron microscopy (TEM), X-ray diffraction (XRD), and UV-visible spectroscopy. The TEM images reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Toluene was taken as the target VOC mainly because it is one of the most common pollutants both indoors or outdoors [28,29]. Furthermore, there have been many studies on the photocatalytic degradation of toluene, and thus there is a sufficient theoretical basis and practical feasibility [30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Toluene was taken as the target VOC mainly because it is one of the most common pollutants both indoors or outdoors [28,29]. Furthermore, there have been many studies on the photocatalytic degradation of toluene, and thus there is a sufficient theoretical basis and practical feasibility [30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, under high initial concentration conditions, fewer sites are available for adsorption of the target chemicals before the surface reactions occur, suggesting that the adsorption process is the ratedetermining step for photocatalysis of the target pollutants over GTCNs. Similarly, recent studies 31,32 have found that the photocatalytic activities determined using other types of catalysts or reactor systems, with respect to the degradation of selected gaseous and aqueous contaminants, were lower under high initial concentration conditions. Specifically, Jo et al 32 noted that the decomposition efficiencies for gaseous benzene, toluene, ethylbenzene, and o-xylene over visible-lightactivated rod-shaped TiO 2 in a plug-flow reactor decreased from 19% to 2%, 53% to 8%, 85% to 17%, and 92% to 33%, respectively, when the concentration of these chemicals was raised from 0.1 to 2.0 ppm.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 76%
“…Similarly, recent studies 31,32 have found that the photocatalytic activities determined using other types of catalysts or reactor systems, with respect to the degradation of selected gaseous and aqueous contaminants, were lower under high initial concentration conditions. Specifically, Jo et al 32 noted that the decomposition efficiencies for gaseous benzene, toluene, ethylbenzene, and o-xylene over visible-lightactivated rod-shaped TiO 2 in a plug-flow reactor decreased from 19% to 2%, 53% to 8%, 85% to 17%, and 92% to 33%, respectively, when the concentration of these chemicals was raised from 0.1 to 2.0 ppm. Romaõ et al 33 stated that the PDE of cortisone acetate, as determined using P25 TiO 2 suspended in a water-containing batch reactor under UV irradiation, decreased gradually as the initial concentration of this compound increased from 5 to 40 mg L −1 .…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 76%